Webs of Affection and Obligation: Glimpse into Families and Nineteenth Century Transatlantic Communities - Errington, Elizabeth (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2008)
AbstractThis paper explores the networks of affection, of frustration, and of obligation that continued to tie families and friends divided by the Atlantic in the first half of the nineteenth century as seen through the correspondence of two men — John Gemmill, who with his wife and 7 children emigrated to Upper Canada in the 1820s, and John Turner, who stayed home in England after his younger brother resettled in St. Andrews, New Brunswick in the 1830s. A close reading of this correspondence illustrates how kith and kin divided by the Atlantic continued to assert their place around family firesides, despite the difficulties presented by the gulf of time and space. Through their letters, correspondents on both sides of the Atlantic also negotiated often highly contested relationships that changed over time. At the same time, this link offered emigrants some reassurance of who they were and their place in the world as they negotiated new identities.